Single molecule electron transfer dynamics in complex environments - Leite, VBP; Alonso, LCP; Newton, M.; Wang, J. (American Physical Soc, 2005)
We propose a new theoretical approach to study the kinetics of the electron transfer (ET) under the dynamical influence of the complex environments with the first passage times (FPT) of the reaction events. By measuring the mean and high order moments of FPT and their ratios, the full kinetics of ET, especially the dynamical transitions across different temperature zones, is revealed. The potential applications of the current results to single molecule electron transfer are discussed.